Content validity of STEMIP using CVR method - Ramli, Nur Farhana; Talib, Othman; Abdul Manaf, Umi Kalthom; Hassan, Siti Aishah (Human Resource Management Academic Research Society, 2018)
This study aims to examine the content validity of STEM Teachers’ Instructional Preparedness (STEMTIP) for Malaysian science teachers using Content Validity Ratio (CVR). Fifteen experts selected via purposive sampling evaluated the content. Eight professional university experts in science, psychometrics, curriculum & instructional, and linguistics, and seven science teachers were consulted. The instrument involved 51 items with five main constructs. The results showed that the instrument has a good content validity and proved that STEMTIP has a great potential to be promoted as a good instrument to measure teachers’ STEM instructional preparedness. More sophisticated statistical analysis, such as Rasch Model, will be implemented to obtain more information from the newly developed instrument.